1995
DOI: 10.1139/v95-257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the degree of neutralization on the micellization of block ionomers

Abstract: Abstract:The effect of neutralization on the micellization of polystyrene-b-poly(acry1ic acid) (PS-b-PAA) was investigated by static light scattering (SLS) and small-angle X-ray scattering (SAXS). The block copolymers, present initially in single chain form in either dioxane or benzene-methanol (90110 (vlv)), were neutralized to different degrees by the addition of cesium hydroxide dissolved in methanol. The solutions were simultaneously monitored by SLS. It was found that micelle formation began near 5% neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As previously stated, it has been found that block ionomer micelles, in their final state, are kinetically-frozen aggregates that do not exhibit dynamic equilibrium, even under high-temperature conditions . However, it is believed that rapid exchange between micelles and unimers does exist in the early stages of micellization, when the ion content of the insoluble blocks is relatively low and micelle lability is enhanced by solvent swelling . As the degree of neutralization increases, solvent is expelled from the micelle and the core becomes increasingly viscous and compact.…”
Section: Resultsmentioning
confidence: 98%
“…As previously stated, it has been found that block ionomer micelles, in their final state, are kinetically-frozen aggregates that do not exhibit dynamic equilibrium, even under high-temperature conditions . However, it is believed that rapid exchange between micelles and unimers does exist in the early stages of micellization, when the ion content of the insoluble blocks is relatively low and micelle lability is enhanced by solvent swelling . As the degree of neutralization increases, solvent is expelled from the micelle and the core becomes increasingly viscous and compact.…”
Section: Resultsmentioning
confidence: 98%
“…It should be noted that the trends which are observed in the aggregation numbers for these samples which have relatively short insoluble block lengths (0.4−3 mol %) may not necessarily be indicative of the behavior for higher ionic block lengths. For instance, a recent paper probed the effect of different degrees of neutralization on the micellization of two block copolymer samples, PS(600) -b- PAA(34) and PS(600) -b- PAA(45) . In that study, the aggregation numbers in toluene for the acid block copolymers were found to be lower than those of the sodium neutralized samples.…”
Section: Resultsmentioning
confidence: 99%
“…Micellization of block ionomers has been studied extensively in this laboratory , as well as in others. Block ionomer micelles have been shown to possess several characteristic features. For instance, they have been found to be extremely stable. , This stability allows for the characterization of the micelles by SEC. , In general, two peaks could be identified from the SEC chromatograms, one corresponding to the micellized block copolymer and the other due to block copolymers present as single chains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution‐ and micelle‐forming behaviors of the block copolymers constituting with hydrophilic poly(ethylene oxide) and hydrophobic poly(propylene oxide) blocks have also been studied in detail 9. Self‐assembling and nanocomposite formation of polystyrene‐ b ‐poly(4‐vinyl pyridine),10 polystyrene‐ b ‐poly(acrylic acid),11 and poly(ethylene oxide)‐ b ‐poly(butylene oxide)12 have been investigated in various solvent systems.…”
Section: Introductionmentioning
confidence: 99%